2018
DOI: 10.1007/s10803-018-3776-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Transition to University Programme for Students with Autism Spectrum Disorder

Abstract: Applying to university can be an anxiety-provoking time for many autistic students, though enrolment can be increased by actively involving them in transition planning. We provide an evaluation of a transition to university pilot programme (Autism Summer School) for autistic students (16-19 years) who are seeking to apply/attend university. The content focused on introducing students to various aspects of university life including academic (sample lectures), social (e.g., clubs and societies), and daily living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Those who graduated likely still had social difficulties (Cai & Richdale, 2016) but may have nonetheless formed a sense of belonging. For example, university has been noted as offering social opportunity for autistic people, through finding like-minded others and offering structured social activities (Lei et al, 2018). In the current study, qualitative data also showed that those who did not complete uniquely described having limited or superficial friendships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who graduated likely still had social difficulties (Cai & Richdale, 2016) but may have nonetheless formed a sense of belonging. For example, university has been noted as offering social opportunity for autistic people, through finding like-minded others and offering structured social activities (Lei et al, 2018). In the current study, qualitative data also showed that those who did not complete uniquely described having limited or superficial friendships.…”
Section: Discussionmentioning
confidence: 99%
“…Toor et al (2016) describe how reliable, appropriately trained designated contacts during the transition period could help autistic people better navigate this process. Lei, Calley, Brosnan, Ashwin and Russell (2018) evaluated a transition programme for autistic young people considering applying to university. The programme gave a 'taste' of university life, covering academic, social and wellbeing aspects of university.…”
Section: Discussionmentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental condition characterised by social communication difficulties and restricted and repetitive behaviours (American Psychiatric Association 2013) affecting up to 1 in 59 children (Centers for Disease Control and Prevention 2019). For many students on the autism spectrum, the inherent social communication difference not only affects their ability to establish a new functional social network at university, but also interfere with academic work such as doing group projects, and living in shared accommodation (Adreon and Durocher 2007;Gelbar et al 2014;Lambe et al 2018;Lei et al 2019Lei et al , 2018. Many students on the autism spectrum report high levels of anxiety (71%), loneliness (53%), and depression (47%) (Gelbar et al 2014), as well as elevated rates of suicidal ideation and attempts (Jackson et al 2018a) as a result of poor university adaptation.…”
Section: Autistic Traits and University Transition Outcomesmentioning
confidence: 99%
“…It has long been recognised that university transition can be a stressful time (Compas et al 1986;Felner et al 1983;Lambe et al 2018;Lei et al 2018), as students separate from established social networks at home, adjust to independent living and build new ties to integrate into the university community (Tinto 1988;Van Gennep 1960). Students who experience high levels of social anxiety (de Lijster et al 2018), or social communication differences and a preference for sameness as exemplified by high levels of autistic traits (Jobe and Williams White 2007) may find such social network changes particularly challenging, which in turn may impact on university transition outcomes.…”
mentioning
confidence: 99%
“…As research on the transition to postsecondary settings receives increasing attention, interventions aimed at supporting youth during these periods are being examined for their efficacy. For example, Lei and colleagues [73] implemented a 3-day, overnight summer school program in the UK for youth with ASD, ages 16 or older, who are preparing for university life. The curriculum included lessons on 'work' (i.e., experiencing a typical lecture, appropriate socialization between students and faculty/staff, and disclosure of diagnosis), 'rest' (i.e., stress reduction, management of anxiety, and the importance of physical wellbeing), and 'play' (i.e., on-campus clubs and societies, social outings, and informal social experiences).…”
Section: Transitioning To the Universitymentioning
confidence: 99%